Performing preemption. (October 2014) - de Goede, Marieke; Simon, Stephanie; Hoijtink, Marijn
Nearly 15 years after 9/11, it is time to grapple with the way in which imperatives of preemption have made their way into routine security practice and bureaucratic operations. As a growing literature in security studies and political geography has argued, preparing for catastrophe, expecting the worst, and scripting disasters are central elements of contemporary, speculative security culture. One of the most-discussed findings of the 9/11 Commission Report was that US security services had insufficiently deployed their imagination to foresee and preempt the attacks. This article introduces a special issue that offers a range of in-depth empirical studies that analyse how the imperative of 'routinizing the imagination' plays out in practice across different policy domains. It deploys the lens of performativity in order to conceptualize and explain the materialization of preemption and its situated entanglements with pre-existing security bureaucracies. We detail the idealized traits of a 'security of the interstice', which include interoperability, emergence, flexibility and analytical foresight that are meant to bridge the perceived gaps of security spaces and the temporal bridges between present and possible futures. The lofty rhetoric of preparing for the worst and bridging the gaps encounters numerous obstacles, challenges and reversals in practice . As becomes clear through the notion of performativity, such obstacles and challenges do not just 'stand in the way' of implementation, but actively shape the materialization of preemption in different sectors.